Evaluation of User Satisfaction of New Student Admission System Using End User Computing Satisfaction Model (Elkom: Jurnal Elektronika dan Komputer, 2026)
Evaluation of information systems should not only focus on technical aspects but also consider user satisfaction. User satisfaction serves as an important indicator for assessing system quality and guiding future improvements. This study aims to evaluate user satisfaction with the New Student Admission (PMB) information system using the End User Computing Satisfaction (EUCS) model, which consists of five dimensions: content, accuracy, format, ease of use, and timeliness. Data were collected through a questionnaire consisting of 12 Likert-scale questions administered to 139 respondents. The results indicate an overall user satisfaction score of 3.78, suggesting that the PMB information system is considered satisfactory. The highest-rated dimension was format (3.98), indicating that the system’s information presentation met user expectations. However, the scores have not reached the maximum, highlighting room for further improvement of the system.